Age cohort effects on unemployment in the US: Evidence from the regional level - Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2020)
Since the early 1970s, it was argued that shifts from relatively smaller to larger youth cohorts in the labor force raise the unemploy- ment rate. In contrast, Shimer (2001) comes to a contrary conclusion using US state level data. I provide a theoretical framework for local labor markets that considers age cohort differences in labor market characteristics. Using a spatial panel data model and US county level data (2000-2014), the estimates provide strong evidence that aging of the working age population reduces overall unemployment by almost one percentage point. Long-run effects that consider local feedbacks are even larger.
Keywords: J60; R12; J10; C23; 330; Regional Unemployment; Spatial Interactions; Aging; Panel Data; Spatial Model